2012
DOI: 10.7150/ijms.4799
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Polymorphisms of DNA Repair Genes Significantly Modulated Bladder Cancer Risk

et al.

Abstract: DNA repair is a primary defense mechanism against damage caused by exogenous and endogenous sources. We examined the associations between bladder cancer and 7 polymorphisms from 5 genes involved in the maintenance of genetic stability (MMR: MLH1-93G>A; BER: XRCC1--77T>C and Arg399Gln; NER:XPC Lys939Gln and PAT +/-; DSBR:ATM G5557A and XRCC7 G6721T) in 302 incident bladder cancer cases and 311 hospital controls. Genotyping was done using a polymerase chain reaction restriction fragment length polymorphism (PCR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Thus, XRCC1 deficiency might increase cancer risk by promoting genomic instability. Certain polymorphic variants of human XRCC1 (e.g., R399G, R194W) have been associated with increased risk of cancer in the ovary, bladder, stomach, pancreatic, colon, skin, lung and of chronic myeloid leukemia [149154]. Furthermore, it has been reported that XRCC1 is frequently mutated in familial breast and ovarian cancer [155157,83].…”
Section: Defects In Accessory Proteins Ber Deficiency and Human Disementioning
confidence: 99%
“…Thus, XRCC1 deficiency might increase cancer risk by promoting genomic instability. Certain polymorphic variants of human XRCC1 (e.g., R399G, R194W) have been associated with increased risk of cancer in the ovary, bladder, stomach, pancreatic, colon, skin, lung and of chronic myeloid leukemia [149154]. Furthermore, it has been reported that XRCC1 is frequently mutated in familial breast and ovarian cancer [155157,83].…”
Section: Defects In Accessory Proteins Ber Deficiency and Human Disementioning
confidence: 99%
“…Table 1 showed the characteristics of all the eligible studies and genotype frequency distributions of twelve polymorphisms in five XRCC genes ( XRCC1 -rs915927, XRCC1 -rs25489, XRCC1 -rs25487, XRCC1 -rs1799782, XRCC1 -rs3213245, XRCC2 -rs3218536, XRCC3 -rs1799796, XRCC3 -rs861539, XRCC4 -rs6869366, XRCC4 -rs28360071, XRCC4 -rs1805377, XRCC7 -rs7003908) included in current meta-analysis (Agalliu et al, 2010, Andrew et al, 2015, Andrew et al, 2007, Andrew et al, 2006, Arizono et al, 2008, Berhane et al, 2012, Broberg et al, 2005, Chang et al, 2009, Lan et al, 2006, Lavender et al, 2010, Chang et al, 2008, Dhillon et al, 2009, Figueroa et al, 2007a, Figueroa et al, 2007b, Fontana et al, 2008, Gangwar et al, 2009, Hamano et al, 2008, Hirata et al, 2006, Hirata et al, 2007, Huang et al, 2007, Abe et al, 2011, Mittal et al, 2008, Narter et al, 2009, Nowacka-Zawisza et al, 2015, Ramaniuk et al, 2014, Ritchey et al, 2005, Rybicki et al, 2004, Sak et al, 2007, Sanyal et al, 2004, Shen et al, 2003, Stern et al, 2002, Stern et al, 2001, Van Gils et al, 2002, Wang et al, 2010, Wang et al, 2008, Wen et al, 2009, Wen et al, 2013, Wu et al, 2006, Xu et al, 2007, Zhi et al, 2012, Hao et al, 2008, Zhou et al, 2012, Zhu et al, 2014, Zhu et al, 2012, Kelsey et al, 2004, Kuasne et al, 2011, Luedeke et al, 2009, Mandal et al, 2010, Mandal et al, 2011, Matullo, 2005, Matullo et al, 2006, Matullo et al, 2001, Mittal et al, 2012a, Mittal et al, 2012b). The study selection processes were presented in Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic polymorphisms of XRCC7 6721G>T were associated with an increased risk of glioma [22], bladder cancer [28], and SLE [30], while other studies reported that there were no significant associations between this polymorphism and risk of renal cell carcinoma and differentiated thyroid cancer [24, 29]. Our result further supports that the polymorphism of the XRCC 7 6721G>T may be a genetic risk factor for azoospermic male infertile but not for total infertile and severe oligozoospermia (Table 3).…”
Section: Discussionmentioning
confidence: 99%